Epigenetic Changes Associated With Exposure to Glyphosate-Based Herbicides in Mammals - Rossetti, María Florencia; Canesini, Guillermina; Lorenz, Virginia; Milesi, María Mercedes; Varayoud, Jorgelina; Ramos, Jorge Guillermo (Frontiers in Endocrinology, 2021)
Glyphosate is a phosphonomethyl amino acid derivative present in a number of non-selective and systemic herbicides. During the last years the use of glyphosate-based herbicide (GBH) has been increasing exponentially around the world, including Argentina. This fact added to the detection of glyphosate and its main metabolite, amino methylphosphonic acid (AMPA), in environmental matrices such as soil, sediments and food, has generated great concern about its risks for humans, animals and environment. During the last years, there were controversy and intense debate regarding the toxicological effects of these compounds associated with endocrine system, cancer, reproduction and development. The mechanisms of action of GBH and their metabolites are still under investigation, although recent findings have shown that could comprise epigenetic modifications. These are reversible mechanisms linked to tissue-specific silencing of gene expression, genomic imprinting and tumor growth. Particularly, glyphosate, GBH and AMPA have been reported to produce changes in global DNA methylation, methylation of specific genes, histone modification and differential expression of non-coding RNAs in human cells and rodents. Importantly, the epigenome could be heritable and could lead to disease long after the exposure has ended. This mini-review summarizes the epigenetic changes produced by glyphosate, GBHs and AMPA in human and rodents and proposes it as a potential mechanism of action through which these chemical compounds could alter body functions.